Cervical cancer and sanitation components in the municipalities of the state of Mato Grosso do Sul: would it be a question of poor water quality? - Silva, Julio Cesar; Machado, Carlos; Nunes, Daniele (Saúde e Sociedade, 2022)
This article investigates relationships between the incidence of cervical cancer (CCI) and the water components and quality indicators, in the municipalities of Mato Grosso do Sul, between 2014 and 2017, by statistical (Pearson’s Determinant) and spatial (k-means Clustering) correlation. There was a greater statistical response of CCI in relation to the average tariff of the practiced supply (−36.28%) and water (−34.15%) services; the number of their systematic interruptions (28.3%) and outages (22.28%); the average per capita consumption of water (20.74%); and the number of services performed (−17.98%), all answers under p-value ≤ 0.001. In Costa Rica, city with the highest average CCI, the spatial clustering identified a greater effect of those interruptions (z-value = 8.741) and outages (z = 7.6097); whereas, in Rochedo, also under high CCI, the analyses showed greater effect with non-standard results for total coliforms (z = 8.6803) and turbidity (z = 5.7427), under a statistical correlation of 12.05% (p-value = 0.032) and 15.18% (p-value = 0.007), respectively. Data from SISAGUA revealed the presence of coliforms and high levels of turbidity, for example, in Antônio João and Tacuru, cities with high average ICC. We recommend further investigation into the relationships presented here between CCI and water.